High-bearing engineering plastic worm wheel applied to light truck electric power steering system and manufacturing process

By fluorination activation and plasma treatment of the polymer substrate, combined with gradient cooling and annealing treatment, and designing the micro-texture structure, the problem of poor interface compatibility of the worm gear was solved, and a worm gear transmission effect with high load-bearing strength and long life was achieved.

CN120795596APending Publication Date: 2025-10-17ZHEJIANG MAYATA PRECISION MASCH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511152880.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

During the worm gear injection molding process, the interface compatibility between the molten polymer and the reinforcing fiber is poor, which makes it difficult to control the interface bonding state, resulting in delamination defects and uneven stress distribution, affecting the load-bearing life of the worm gear.

Method used

By drying the polymer substrate and performing surface fluorination treatment on the polymer substrate, the polymer substrate is subjected to fluorination activation treatment, combined with plasma treatment to enhance the composite, a modified reinforced composite is formed, and gradient cooling and annealing treatment are implemented during the injection molding process to design the micro-texture structure and form a multi-level reinforcement network and an adaptive lubricating film layer.

Benefits of technology

It improves the interface compatibility and overall bearing strength of the worm gear, suppresses stress concentration and tooth shape distortion, achieves structural stability and long-life transmission under high load, and reduces friction noise and wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention relates to the technical field of mechanical parts, and discloses a high-bearing engineering plastic worm gear applied to a light truck electric power steering system and a manufacturing process, and the manufacturing process comprises the following steps: pretreatment of a polymer base material, preparation of a composite reinforcing material, preparation of an injection molding raw material, precise injection molding, post-treatment and detection. After a polymer base material is subjected to fluorination activation treatment, the surface energy of the material is reduced, the interfacial compatibility with a composite reinforced material is enhanced, and through the synergistic effect of chemical bonding and physical anchoring formed between matrix resin and a modified reinforcement body, the interfacial layering tendency of engineering plastic and a fiber reinforced phase is overcome, so that stress transmission is more uniform; meanwhile, the functional additive components generate an in-situ synergistic effect in the precise injection molding process, and form a multi-stage enhanced network with matrix resin, so that the worm wheel matrix is endowed with excellent overall bearing strength and fatigue fracture resistance, and the structural integrity under the working conditions of high load and high-frequency steering is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of mechanical parts, in particular to a high-load-bearing engineering plastic worm wheel applied to a light truck electric power-assisted steering system and a manufacturing process. BACKGROUND

[0002] The plastic worm wheel is a common mechanical part, mainly applied to an aero-engine, a gas turbine and a steam turbine machine, has low friction coefficient, good wear resistance and high transmission efficiency, can operate under no-lubrication or little-lubrication conditions, has good elasticity, can absorb shock and prevent impact, has low noise during operation and stable transmission, and the electric power-assisted steering system is a power steering system directly relying on an electric motor to provide auxiliary torque, mainly composed of a torque sensor, a vehicle speed sensor, an electric motor, a speed reduction mechanism and an electronic control unit.

[0003] At present, due to the difference in interface compatibility between the molten polymer and the reinforcing fiber during the injection molding manufacturing process of the worm wheel, the bonding state of the fiber-matrix interface cannot be controlled in real time when the worm wheel structure is formed, when the interface appears delamination defects, the stress distribution of the worm wheel under alternating load is uneven, and when the interface bonding strength is insufficient, the micro-cracks at the tooth root of the worm wheel cannot be warned, further causing the reduction of the load-bearing life of the worm wheel.

[0004] Therefore, the application provides the high-load-bearing engineering plastic worm wheel applied to the light truck electric power-assisted steering system and the manufacturing process to solve the above problems. SUMMARY

[0005] The main purpose of the application is to provide the high-load-bearing engineering plastic worm wheel applied to the light truck electric power-assisted steering system and the manufacturing process to solve the problems in the background.

[0006] To achieve the above purpose, the technical scheme adopted by the application is as follows: the high-load-bearing engineering plastic worm wheel applied to the light truck electric power-assisted steering system and the manufacturing process, comprising the following steps:

[0007] Step 1: polymer substrate pretreatment, selecting polyether ether ketone resin particles, the particle size of the polyether ether ketone resin particles is 0.5-1.5 mm, and the polyether ether ketone resin particles are subjected to drying and surface activation treatment;

[0008] Step 2: composite reinforcing material preparation, mixing a functional additive and reinforcing fibers and then subjecting the mixture to plasma treatment to obtain a modified reinforcing composite;

[0009] Step 3: injection molding raw material preparation, mixing the pretreated polyether ether ketone resin particles, the modified reinforcing composite, a lubricant and a heat stabilizer in proportion;

[0010] Step four: precision injection molding, the mixture is injected into the worm gear mold, control the injection temperature, pressure and cooling gradient;

[0011] Step five: post-processing and detection, annealing treatment, tooth profile finishing and bearing performance test are carried out on the molded worm gear;

[0012] In step three, the injection material is made of the following raw materials by weight: polyether ether ketone resin 70-85 parts, modified reinforcing composite 10-20 parts, lubricant 3-8 parts, and thermal stabilizer 2-5 parts.

[0013] Preferably, step one includes: placing polyether ether ketone resin particles in a vacuum drying box, drying at 120-140℃ for 2-4 hours, then transferring to a reaction kettle, injecting fluorine-containing activation gas, controlling the gas pressure at 0.1-0.3MPa, and stirring at 200-400r / min for 30-60 minutes to complete the surface fluorination treatment.

[0014] Preferably, the fluorine-containing activation gas is a mixture of carbon tetrafluoride and argon gas, with a volume ratio of 1:5-1:8, and the contact angle of the resin particle surface after fluorination is less than 85°.

[0015] Preferably, the preparation of the modified reinforcing composite in step two includes:

[0016] Plasma treatment is carried out in a low-pressure environment of 10-30Pa, increasing the mean free path of nitrogen plasma, so that high-energy particles fully impact the surface of carbon fibers. Under this condition, ceramic particles form nanoscale pits on the surface of the fibers, with a SEM observation depth of 50-100nm. At the same time, active nitrogen radicals in the nitrogen plasma react with carboxyl groups on the surface of carbon fibers to form C-N covalent bonds.

[0017] The carbon fibers and ceramic particles are mixed in a mass ratio of 3:1-5:1, the length of the carbon fibers is 50-100μm, and the ceramic particles are alumina or silicon nitride with a particle size of 10-30μm.

[0018] The mixture is placed in a plasma reaction chamber, vacuumed to 5× -1× Pa, nitrogen gas is introduced to maintain the gas pressure at 10-30Pa, and treated at a power of 500-800W for 10-20 minutes.

[0019] Preferably, the lubricant is a polytetrafluoroethylene micro-powder and silicone composite with a mass ratio of 2:1 and a particle size D50=5-15μm; the thermal stabilizer is a copper-organic complex and a phosphite ester compounded at a ratio of 1:2.

[0020] Preferably, in step four:

[0021] Injection temperature zoning control: barrel zone 1 335-345℃, zone 2 365-375℃, nozzle 375-385℃;

[0022] Injection pressure 120-150MPa, holding pressure 80-100MPa;

[0023] Cooling adopts gradient cooling: first stage high-speed cooling, melt passes through polyether ether ketone glass transition temperature, Tg≈143℃, at a rate of 15-20℃ / s above 280℃, inhibiting spherulite overgrowth, DSC detects spherulite size ≤10μm; second stage slow cooling, cooling rate is reduced at a rate of 5-8℃ / s in the interval of 120-280℃, allowing molecular chains to arrange in order.

[0024] Preferably, the step five comprises:

[0025] Place the worm gear in a nitrogen environment, and heat it to 195-205℃ at a rate of 1-2℃ / min, and then cool it with the furnace after holding for 1-2 hours;

[0026] Use a laser shaping instrument to finish machining the tooth surface, and the tooth shape error is less than 0.02mm;

[0027] Apply 300N·m alternating load on the torque test bench for 10 6 times of cycles, and the tooth surface wear depth is less than 0.05mm.

[0028] Preferably, the engineering plastic worm gear comprises:

[0029] The worm gear base is a polyether ether ketone composite material, and the density is 1.45-1.55g / cm³;

[0030] The gear structure comprises an involute tooth profile, a pressure angle of 19.5-20.5°, and a helix angle of 15-25°;

[0031] The inner wall of the hub is provided with reinforcing ribs, and the rib thickness is 0.8-1.2 times the wall thickness.

[0032] Preferably, the worm gear tooth surface has a micro-texture structure:

[0033] The surface is distributed with micro-pits with a diameter of 50-100μm, and the pit depth is 10-30μm;

[0034] The pit density is 100-200 / mm², and the pits are arranged in a spiral line array;

[0035] The pits are filled with a molybdenum disulfide solid lubricating film, and the film thickness is 2-5μm.

[0036] Preferably, the engineering plastic worm gear satisfies:

[0037] The bending strength is greater than 180 MPa and the compressive strength is greater than 200 MPa at a working temperature of 120 DEG C;

[0038] The noise value is less than 65 dB(A)@3000 rpm when meshing with a metal worm;

[0039] Chemical corrosion resistance: the mass change rate meets 0.3% after soaking in gear oil for 500 hours.

[0040] The present application has the following beneficial effects:

[0041] 1. In the present application, the surface energy of the polymer substrate is reduced after fluorination activation treatment, the interfacial compatibility with the composite reinforcing material is enhanced, the chemical bonding and physical anchoring between the matrix resin and the modified reinforcing body are synergistically combined, the interfacial delamination tendency of the engineering plastic and the fiber reinforced phase is overcome, and the stress transmission is more uniform; at the same time, the functional additive components produce in-situ synergistic effect in the precision injection molding process, form a multi-level reinforced network with the matrix resin, and endow the worm gear matrix with excellent overall bearing strength and anti-fatigue fracture capacity, and ensure the structural integrity under high load and high frequency steering conditions.

[0042] 2. In the present application, the gradient cooling process implemented in the injection molding stage can relieve the internal residual stress concentration of the product by controlling the melt crystallization rate and molecular chain orientation; at the same time, combined with a specific annealing process, the microphase state of the composite material is reorganized and the local internal stress is released, the risk of tooth shape distortion and size instability caused by thermal expansion difference of the worm gear in high and low temperature alternating environment or long term service is inhibited, and the geometric precision and position stability of the worm gear meshing transmission with the metal worm are ensured.

[0043] 3. In the present application, the combination of tooth surface micro-texturing design and solid lubricating medium can continuously release lubricating components through the oil storage effect of the micro-pit array to form an adaptive lubricating film layer at the meshing contact interface; combined with the load support effect of the reinforcing fiber and ceramic particles at the friction interface, the adhesive wear and ploughing effect between the tooth surfaces are reduced, the generation of abnormal vibration and noise under high temperature and high speed conditions is simultaneously inhibited, and the synergistic improvement of the worm gear transmission system in silence, wear resistance and long service life is realized. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0045] Implementation one: a high load-bearing engineering plastic worm wheel applied to a light truck electric power steering system and a manufacturing process, comprising the following steps:

[0046] Step one: polymer substrate pretreatment, select polyether ether ketone resin particles, the particle size of the polyether ether ketone resin particles is 0.5mm, dry and surface activation treatment is carried out on it;

[0047] Step two: composite reinforcing material preparation, after mixing the functional additives and reinforcing fibers, plasma treatment is carried out to obtain a modified reinforcing composite, the functional additives are silane coupling agent KH-550, after hydrolysis, the silanol group produced by the silane coupling agent KH-550 condenses with the surface hydroxyl group of the carbon fiber to form a-Si-O-C- covalent bond, and the FTIR spectrum appears a characteristic peak at 1110 , and the compatibility of the organic long-chain reinforcing agent with the resin is good, and the addition amount is 1.5% of the mass of the carbon fiber.

[0048] Step three: injection molding raw material preparation, mix the pretreated polyether ether ketone resin particles with the modified reinforcing composite, lubricant and heat stabilizer according to the proportion;

[0049] Step four: precision injection molding, inject the mixture into the worm wheel mold, control the injection temperature, pressure and cooling gradient;

[0050] Step five: post-processing and detection, annealing treatment, tooth shape finishing and bearing performance test are carried out on the formed worm wheel;

[0051] In step three, the injection molding raw material is prepared from the following weight parts of raw materials: polyether ether ketone resin 70 parts, modified reinforcing composite 10 parts, lubricant 3 parts, and heat stabilizer 2 parts.

[0052] Step one includes: placing the polyether ether ketone resin particles in a vacuum drying oven, drying at 120℃ for 2 hours, then transferring to a reaction kettle, injecting fluorine-containing activation gas, controlling the gas pressure at 0.1MPa, and stirring at 200r / min for 30 minutes to complete the surface fluorination treatment.

[0053] The fluorine-containing activation gas is a mixture of carbon tetrafluoride and argon gas, and the volume ratio of the mixture is 1:5. The contact angle of the resin particles after fluorination treatment is less than 85°.

[0054] The preparation of the modified reinforcing composite in step two includes:

[0055] The plasma treatment is performed in a low pressure environment of 10 Pa, increasing the mean free path of nitrogen plasma, so that high-energy particles can fully impact the surface of carbon fibers. Under this condition, ceramic particles form nanoscale pits on the surface of the fibers, and the depth of SEM observation is 50 nm, which increases the specific surface area and produces a mechanical anchoring effect. At the same time, active nitrogen radicals in the nitrogen plasma react with carboxyl groups on the surface of the carbon fibers to form C-N covalent bonds, and the content of surface nitrogen elements is increased by 8% through XPS detection. Both of them ensure that the interface bonding strength of the modified and reinforced composite with the resin matrix is ≥45 MPa.

[0056] The carbon fibers and ceramic particles are mixed in a mass ratio of 3:1, the length of the carbon fibers is 50 μm, and the ceramic particles are aluminum oxide or silicon nitride with a particle size of 10 μm.

[0057] The mixture is placed in a plasma reaction chamber, vacuumed to 5× -1× Pa, nitrogen gas is introduced to maintain a pressure of 10 Pa, and treated at a power of 500 W for 10 minutes.

[0058] The lubricant is a polytetrafluoroethylene micro-powder and silicone compound with a mass ratio of 2:1 and a particle size of D50=5 μm; the thermal stabilizer is a copper-organic complex and a phosphite ester compounded in a ratio of 1:2.

[0059] In step four:

[0060] The injection temperature is controlled in zones: the barrel is controlled in two zones at 335℃ and 365℃, and the nozzle is controlled at 375℃.

[0061] The injection pressure is 120 MPa, and the holding pressure is 80 MPa.

[0062] The cooling is performed in a gradient cooling mode: in the first stage, the melt is cooled at a high speed of 15℃ / s above the glass transition temperature of polyether ether ketone, Tg≈143℃, to inhibit the excessive growth of spherulites, and the size of the spherulites is ≤10 μm detected by DSC; in the second stage, the cooling rate is reduced at a low speed of 5℃ / s at 120℃, so that the molecular chains are arranged in order, the crystallinity is increased to 35% as shown by XRD, and the residual stress is reduced by 40% measured by photoelastic method.

[0063] Step five includes:

[0064] The worm gear is placed in a nitrogen environment, and heated to 195℃ at a rate of 1℃ / min, and then cooled with the furnace after holding for 1 hour;

[0065] The laser shaping instrument is used for finishing the tooth surface, and the tooth shape error is less than 0.02 mm.

[0066] An alternating load of 300 N·m is applied on the torque test bench for 10,000 cycles, and the tooth surface wear depth is less than 0.05 mm.

[0067] The plastic worm gear comprises:

[0068] The worm gear base is a polyether ether ketone composite material with a density of 1.45 g / cm³;

[0069] The tooth structure comprises an involute tooth profile, a pressure angle of 19.5°, and a helix angle of 15°;

[0070] The inner wall of the hub is provided with a reinforcing rib, and the rib thickness is 0.8 times the wall thickness.

[0071] The worm gear tooth surface has a micro-texture structure:

[0072] The surface is distributed with micro-pits with a diameter of 50 μm, and the pit depth is 10 μm;

[0073] The pit density is 100 / mm², and the pits are arranged in a spiral line array;

[0074] The pit is filled with a solid lubricating film of molybdenum disulfide, and the film thickness is 2 μm.

[0075] The engineering plastic worm gear meets:

[0076] At a working temperature of 120°C, the bending strength is greater than 180 MPa, and the compressive strength is greater than 200 MPa;

[0077] When meshing with a metal worm, the noise value is less than 65 dB(A) @ 3000 rpm;

[0078] Chemical corrosion resistance: the mass change rate after soaking in gear oil for 500 hours meets 0.3%.

[0079] Implementation II: A high-load engineering plastic worm gear applied to a light truck electric power steering system and a manufacturing process, comprising the following steps:

[0080] Step 1: Polymer substrate pretreatment, select polyether ether ketone resin particles, the particle size of the polyether ether ketone resin particles is 1.0 mm, and dry and surface activation treatment is performed;

[0081] Step 2: Composite reinforcing material preparation, after mixing the functional additives and reinforcing fibers, plasma treatment is performed to obtain a modified reinforcing composite, the functional additives are silane coupling agent KH-550, the silanol groups produced after hydrolysis of the silane coupling agent KH-550 are condensed with the surface hydroxyl groups of the carbon fibers to form -Si-O-C- covalent bonds, and FTIR spectrum appears a characteristic peak at 1110 , and the organic long-chain reinforcing agent is compatible with the resin, and the addition amount is 2.0% of the mass of the carbon fibers.

[0082] Step 3: Injection molding raw material preparation, mix the pretreated polyether ether ketone resin particles, the modified reinforcing composite, the lubricant, and the heat stabilizer in proportion;

[0083] Step four: precision injection molding, injecting the mixture into the worm gear mold, controlling the injection temperature, pressure and cooling gradient;

[0084] Step five: post-processing and testing, annealing the molded worm gear, tooth profile finishing and bearing performance testing;

[0085] In step three, the injection material is made of the following raw materials by weight: polyether ether ketone resin 80 parts, modified reinforcing composite 15 parts, lubricant 5 parts, and thermal stabilizer 3 parts.

[0086] Step one includes: placing polyether ether ketone resin particles in a vacuum drying oven, drying at 130°C for 3 hours, then transferring to a reaction kettle, injecting fluorine-containing activation gas, controlling the gas pressure at 0.2 MPa, and stirring at 300 r / min for 40 minutes to complete the surface fluorination treatment.

[0087] The fluorine-containing activation gas is a mixture of carbon tetrafluoride and argon gas with a volume ratio of 1:6. The contact angle of the resin particles after fluorination treatment is less than 85°.

[0088] The preparation of the modified reinforcing composite in step two includes:

[0089] Plasma treatment is carried out in a low-pressure environment of 20 Pa to increase the mean free path of nitrogen plasma, so that high-energy particles can fully impact the surface of carbon fibers. Under this condition, ceramic particles form nanoscale pits on the surface of the fibers, with a SEM observation depth of 70 nm, increasing the specific surface area and producing a mechanical anchoring effect. At the same time, active nitrogen radicals in the nitrogen plasma react with carboxyl groups on the surface of the carbon fibers to form C-N covalent bonds. The surface nitrogen content increases by 10% as detected by XPS, and the interface bonding strength between the modified reinforcing composite and the resin matrix is ≥45 MPa.

[0090] The carbon fibers and ceramic particles are mixed in a mass ratio of 4:1, the length of the carbon fibers is 80 μm, and the ceramic particles are aluminum oxide or silicon nitride with a particle size of 20 μm.

[0091] The mixture is placed in a plasma reaction chamber, vacuumed to 5× -1× Pa, nitrogen gas is introduced to maintain the pressure at 20 Pa, and treated at a power of 600 W for 15 minutes.

[0092] The lubricant is a polytetrafluoroethylene powder and silicone composite with a mass ratio of 2:1 and a particle size D50=10 μm; the thermal stabilizer is a copper-organic complex and a phosphite ester compounded in a ratio of 1:2.

[0093] In step four:

[0094] Injection temperature zoning control: barrel zone one 340°C, zone two 370°C, nozzle 380°C;

[0095] Injection pressure 130MPa, holding pressure 90MPa;

[0096] The cooling adopts gradient cooling: the first stage is high-speed cooling: the melt is quickly passed through the glass transition temperature of polyetheretherketone (Tg≈143°C) at above 280°C at 17°C / s to inhibit excessive growth of spherulites. The DSC detection spherulite size is ≤10μm; the second stage is slow cooling: the cooling rate is reduced at 6°C / s at 120°C to arrange the molecular chains in an orderly manner. XRD shows that the crystallinity is increased to 36%. At the same time, the residual stress is reduced by 45% as determined by photoelasticity.

[0097] Step five includes:

[0098] Place the worm gear in a nitrogen environment, heat it to 200°C at a rate of 1.5°C / min, hold it for 1.5 hours, and then cool it down in the furnace.

[0099] The tooth surface is finely processed using a laser profiler, and the tooth profile error is less than 0.02mm;

[0100] Apply an alternating load of 300 N·m on the torque test bench After one cycle, the tooth surface wear depth is less than 0.05mm.

[0101] Plastic worm gear includes:

[0102] The worm gear matrix is ​​made of polyetheretherketone composite material with a density of 1.50g / cm³;

[0103] The gear tooth structure includes an involute tooth profile, a pressure angle of 20°, and a helix angle of 20°;

[0104] The inner wall of the hub is provided with reinforcing ribs, and the rib thickness is 1.0 times the wall thickness.

[0105] The worm gear tooth surface has a micro-texture structure:

[0106] The surface is distributed with micro pits with a diameter of 70 μm and a depth of 20 μm;

[0107] The pit density is 150 / mm², arranged in a spiral array;

[0108] The pits are filled with a solid lubricating film of molybdenum disulfide with a thickness of 4 μm.

[0109] Engineering plastic worm gears meet the following requirements:

[0110] At a working temperature of 120°C, the bending strength is greater than 180MPa and the compressive strength is greater than 200MPa;

[0111] When meshing with a metal worm, the noise level is less than 65dB(A)@3000rpm;

[0112] Chemical corrosion resistance: the mass change rate after 500 hours of immersion in gear oil meets 0.3%.

[0113] Implementation three: a high load bearing engineering plastic worm wheel applied to light truck electric power steering system and manufacturing process, comprising the following steps:

[0114] Step one: polymer substrate pretreatment, select polyether ether ketone resin particles, polyether ether ketone resin particle size is 1.5mm, dry and surface activation treatment;

[0115] Step two: composite reinforcing material preparation, after mixing the functional additives and reinforcing fibers are treated by plasma, the modified reinforcing composite is obtained, the functional additives are silane coupling agent KH-550, the silanol groups produced after hydrolysis are condensed with the surface hydroxyl groups of carbon fibers to form-Si-O-C- covalent bond, FTIR spectrum appears characteristic peak at 1110 Place, at the same time, organic long-chain reinforcement and resin compatibility, the addition amount is 1.8% of the mass of carbon fiber.

[0116] Step three: injection molding raw material preparation, mixing pretreated polyether ether ketone resin particles with modified reinforcing composite, lubricant and heat stabilizer according to the proportion;

[0117] Step four: precision injection molding, the mixture is injected into the worm wheel mold, the injection temperature, pressure and cooling gradient are controlled;

[0118] Step five: post-processing and detection, annealing treatment, tooth shape finishing and bearing performance test are carried out on the formed worm wheel;

[0119] In step three, the injection molding raw material is prepared from the following weight parts of raw materials: polyether ether ketone resin 85 parts, modified reinforcing composite 20 parts, lubricant 8 parts and heat stabilizer 5 parts.

[0120] Step one includes: placing polyether ether ketone resin particles in a vacuum drying oven, drying at 140℃ for 4 hours, then transferring to a reaction kettle, injecting fluorine-containing activation gas, controlling gas pressure at 0.3MPa, stirring at 400r / min for 60 minutes to complete surface fluorination treatment.

[0121] The fluorine-containing activation gas is a mixture of carbon tetrafluoride and argon gas, the volume ratio of the mixture is 1:8, and the contact angle of the resin particle surface after fluorination treatment is less than 85°.

[0122] The preparation of modified reinforcing composite in step two includes:

[0123] The plasma treatment is performed in a low-pressure environment of 30 Pa, which can increase the mean free path of nitrogen plasma, so that high-energy particles can fully impact the surface of carbon fibers. Under this condition, ceramic particles form nanoscale pits on the surface of the fibers, and the depth of the pits is 100 nm. The specific surface area is increased, and a mechanical anchoring effect is produced. Meanwhile, active nitrogen radicals in the nitrogen plasma react with carboxyl groups on the surface of the carbon fibers to form C-N covalent bonds. The content of nitrogen elements on the surface is increased by 12% through XPS detection. The combination of the two ensures that the interface bonding strength of the modified and reinforced composite with the resin matrix is ≥45 MPa.

[0124] The carbon fibers and ceramic particles are mixed at a mass ratio of 5:1. The length of the carbon fibers is 100 μm, and the ceramic particles are alumina or silicon nitride with a particle size of 30 μm.

[0125] The mixture is placed in a plasma reaction chamber, and vacuum is extracted to 5× -1× Pa. Nitrogen is introduced to maintain a pressure of 30 Pa, and the treatment is performed at a power of 800 W for 20 minutes.

[0126] The lubricant is a polytetrafluoroethylene micro-powder and silicone compound with a mass ratio of 2:1 and a particle size of D50=15 μm. The thermal stabilizer is a copper-organic complex and a phosphite ester with a ratio of 1:2.

[0127] In step four:

[0128] The injection temperature is controlled in zones: the barrel is controlled at 345℃ in the first zone, 375℃ in the second zone, and 385℃ at the nozzle.

[0129] The injection pressure is 150 MPa, and the holding pressure is 100 MPa.

[0130] The cooling is performed in stages: in the first stage, high-speed cooling is performed at 20℃ / s to make the melt pass through the glass transition temperature (Tg≈143℃) of the polyether ether ketone above 280℃, which inhibits the excessive growth of spherulites, and the size of the spherulites is ≤10 μm as detected by DSC; in the second stage, slow cooling is performed at 8℃ / s to reduce the cooling rate to 120℃, which allows the molecular chains to be arranged in order, and the crystallinity is increased to 38% as shown by XRD, and the residual stress is reduced by 50% as determined by photoelasticity.

[0131] Step five includes:

[0132] The worm gear is placed in a nitrogen environment, and the temperature is increased to 205℃ at a rate of 2℃ / min, and then the furnace is cooled for 2 hours.

[0133] The laser shaping instrument is used to finish machining the tooth surface, and the tooth shape error is less than 0.02 mm.

[0134] On the torque test bench, an alternating load of 300 N·m is applied for each cycle, and the wear depth of the tooth surface is less than 0.05 mm.

[0135] The engineering plastic worm gear comprises:

[0136] The worm gear base is a polyether ether ketone composite material with a density of 1.55 g / cm³;

[0137] The tooth structure comprises an involute tooth profile, a pressure angle of 20.5°, and a helix angle of 25°;

[0138] The inner wall of the hub is provided with a reinforcing rib, and the rib thickness is 1.2 times the wall thickness.

[0139] The worm gear tooth surface has a micro-texture structure:

[0140] The surface is distributed with micro-pits with a diameter of 100 μm, and the pit depth is 30 μm;

[0141] The pit density is 200 pits / mm², and the pits are arranged in a spiral line array;

[0142] The pits are filled with a solid lubricating film of molybdenum disulfide with a film thickness of 5 μm.

[0143] The engineering plastic worm gear meets:

[0144] At a working temperature of 120°C, the bending strength is greater than 180 MPa, and the compressive strength is greater than 200 MPa;

[0145] When meshing with a metal worm, the noise value is less than 65 dB(A) @ 3000 rpm;

[0146] Chemical corrosion resistance: after soaking in gear oil for 500 hours, the mass change rate meets 0.3%.

[0147] Comparative Example 1, the difference between this comparative example and Example 1 is that in the preparation of the composite reinforcing material in step two, no plasma treatment is performed.

[0148] Comparative Example 2, the difference between this comparative example and Example 1 is that in step one, the surface fluorination treatment is omitted, and only the polyether ether ketone resin particles are dried.

[0149] Comparative Example 3, the difference between this comparative example and Example 1 is that in step five, the annealing treatment is cancelled, and the formed worm gear is directly subjected to tooth profile finishing.

[0150] Comparative Example 4, the difference between this comparative example and Example 1 is that in the design of the worm gear structure, no tooth surface micro-texture is provided.

[0151] The high-load-bearing engineering plastic worm gears for light truck electric power steering systems prepared in Examples 1-3 and Comparative Examples 1-4 are subjected to performance testing, and the test items and test methods are as follows:

[0152] Torque strength test, the torque was applied to the worm gear failure on the torque loading device at a rate of 10 N·m / s, and the maximum torque value was recorded;

[0153] Wear resistance test, using a friction and wear testing machine, running 200 km under the condition of contact pressure 10 MPa and sliding speed 0.3 m / s, the tooth surface wear depth was measured;

[0154] Dimensional accuracy test, using a three-coordinate measuring instrument, the geometric accuracy was evaluated according to the tooth profile deviation, tooth deviation and tooth spacing deviation;

[0155] Thermal deformation temperature test, on a thermal deformation Vicat testing machine, the temperature at which the deformation reached 0.2 mm was determined at a bending stress of 0.45 MPa and a temperature rise rate of 2 ℃ / min.

[0156] The test data of the high-load engineering plastic worm gears prepared in Examples 1-3 and Comparative Examples 1-4 are recorded in the following table:

[0157] Test item Torsional strength (N·m) Wear depth (μm) Tooth profile error (mm) Heat distortion temperature (℃) Example 1 382 53±3 0.015±0.002 244 Example 2 376 55±2 0.014±0.003 238 Example 3 386 51±2 0.016±0.002 246 Comparative Example 1 292 118±5 0.037±0.005 204 Comparative Example 2 282 113±4 0.034±0.004 197 Comparative Example 3 262 96±3 0.054±0.006 189 Comparative Example 4 302 143±6 0.024±0.003 212

[0158] By comparing and analyzing the data in the table, it can be seen that the high-load engineering plastic worm gears prepared by the processes in Examples 1-3 have significantly improved performance compared to the worm gears prepared by the processes in Comparative Examples 1-4. This shows that after the polymer substrate is treated by fluorination activation, the surface energy of the material is reduced, the interfacial compatibility with the composite reinforcing material is enhanced, and through the synergistic effect of chemical bonding and physical anchoring between the matrix resin and the modified reinforcing body, the interfacial delamination tendency of the engineering plastic and the fiber reinforcing phase is overcome, and the stress transfer is more uniform; at the same time, the functional additive components produce an in-situ synergistic effect during precision injection molding, forming a multi-level reinforcing network with the matrix resin, giving the worm gear matrix excellent overall load-bearing strength and fatigue fracture resistance, ensuring the structural integrity under high-load and high-frequency steering conditions. The gradient cooling process implemented during injection molding controls the crystallization rate and molecular chain orientation of the melt, relieving the internal residual stress concentration of the product; at the same time, combined with a specific annealing process, the microphase state of the composite material is reorganized and the local internal stress is released, inhibiting the risk of tooth distortion and dimensional instability caused by thermal expansion differences in high-low temperature alternating environments or long-term service, ensuring the geometric accuracy and positional stability of the worm gear and metal worm gear meshing transmission. The design of micro-texturing on the tooth surface and the combined application of solid lubricating medium continuously release the lubricating components through the oil storage effect of the micro-pit array, building an adaptive lubricating film layer at the meshing contact interface; combined with the load-bearing support of reinforcing fibers and ceramic particles at the friction interface, the adhesive wear and plowing effect between the tooth surfaces is reduced, and the generation of abnormal vibration and noise under high temperature and high speed conditions is simultaneously inhibited, achieving the synergistic improvement of silent, wear-resistant and long-life of the worm gear transmission system.

[0159] Through comparison and analysis of the related data in the table, it can be known that the high bearing engineering plastic worm wheel prepared by the forming process has not only excellent torsional strength, wear resistance and dimensional stability, but also temperature self-adaptive lubrication characteristics. Therefore, the engineering plastic worm wheel manufacturing process provided by the application has a broader market prospect and is more suitable for promotion.

[0160] Although embodiments of the application have been shown and described, it would be appreciated by those skilled in the art that changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the application, and the scope of protection of the application is defined by the appended claims and their equivalents.

Claims

1. A manufacturing process for a high-load-bearing engineering plastic worm gear used in a light truck electric power steering system, characterized in that: The following steps are involved: Step 1: Pretreatment of the polymer substrate: selecting polyetheretherketone resin particles with a particle size of 0.5-1.5 mm, drying and surface activation treatment thereof; Step 2: Preparation of composite reinforcement material: mixing the functional additive with the reinforcement fiber and then subjecting it to plasma treatment to obtain a modified reinforcement composite; Step 3: Preparation of injection molding raw materials: mixing the pretreated polyetheretherketone resin particles with the modified reinforced composite, lubricant, and thermal stabilizer in proportion; Step 4: Precision injection molding: inject the mixed material into the worm gear mold and control the injection temperature, pressure and cooling gradient; Step 5: Post-processing and testing: annealing, tooth refinement and load-bearing performance testing of the formed worm gear; In the step 3, the injection molding material is made of the following raw materials in parts by weight: 70-85 parts of polyetheretherketone resin, 10-20 parts of modified reinforced composite, 3-8 parts of lubricant, and 2-5 parts of heat stabilizer.

2. The manufacturing process of a high-load-bearing engineering plastic worm gear for a light truck electric power steering system according to claim 1, characterized in that: The step 1 comprises: placing the polyetheretherketone resin particles in a vacuum drying oven, drying them at 120°C-140°C for 2-4 hours, then transferring them to a reactor, injecting fluorine-containing activation gas, controlling the gas pressure at 0.1-0.3 MPa, and stirring at 200-400 r / min for 30-60 minutes to complete the surface fluorination treatment.

3. The manufacturing process of a high-load-bearing engineering plastic worm gear for a light truck electric power steering system according to claim 1, characterized in that: The fluorine-containing activated gas is a mixture of carbon tetrafluoride and argon, with a mixing volume ratio of 1:5-1:

8. The surface contact angle of the resin particles after fluorination treatment is less than 85°.

4. The manufacturing process of a high-load-bearing engineering plastic worm gear for a light truck electric power steering system according to claim 1, characterized in that: The preparation of the modified and reinforced composite in step 2 includes: Plasma treatment is carried out in a low-pressure environment of 10-30 Pa, which increases the mean free path of nitrogen plasma and allows high-energy particles to fully impact the carbon fiber surface. Under these conditions, ceramic particles form nano-scale pits on the fiber surface, with a SEM observation depth of 50-100nm. At the same time, the active nitrogen radicals in the nitrogen plasma react with the carboxyl groups on the carbon fiber surface to form CN covalent bonds. The carbon fibers and ceramic particles are mixed in a mass ratio of 3:1-5:1, wherein the carbon fibers have a length of 50-100 μm and the ceramic particles are aluminum oxide or silicon nitride with a particle size of 10-30 μm; The mixture was placed in a plasma reaction chamber and vacuumed to 5× –1× Pa, introduce nitrogen to maintain the pressure at 10-30 Pa, and treat at a power of 500-800 W for 10-20 minutes.

5. The manufacturing process of a high-load-bearing engineering plastic worm gear for a light truck electric power steering system according to claim 1, characterized in that: The lubricant is a composite of polytetrafluoroethylene micropowder and silicone in a mass ratio of 2:1, with a particle size D50 of 5-15 μm; the heat stabilizer is a composite of copper-organic complex and phosphite in a ratio of 1:

2.

6. The manufacturing process of a high-load-bearing engineering plastic worm gear for a light truck electric power steering system according to claim 1, characterized in that: In the step 4: Injection molding temperature zone control: barrel zone 1 335℃-345℃, zone 2 365℃-375℃, nozzle 375℃-385℃; Injection pressure 120-150MPa, holding pressure 80-100MPa; Cooling adopts gradient cooling: in the first stage, high-speed cooling is carried out at a rate of 15-20°C / s to make the melt quickly pass through the glass transition temperature of polyetheretherketone (Tg≈143°C) above 280°C, thereby inhibiting excessive growth of spherulites. The DSC test shows that the spherulite size is ≤10μm. In the second stage, slow cooling is carried out at a rate of 5-8°C / s in the range of 120°C-280°C to arrange the molecular chains in an orderly manner.

7. The manufacturing process of a high-load-bearing engineering plastic worm gear for a light truck electric power steering system according to claim 1, characterized in that: The step five includes: Place the worm gear in a nitrogen environment, heat it to 195-205°C at a rate of 1-2°C / min, hold for 1-2 hours, and then cool it down in the furnace. The tooth surface is finely processed using a laser profiler, and the tooth profile error is less than 0.02mm; Apply an alternating load of 300 N·m on the torque test bench After one cycle, the tooth surface wear depth is less than 0.05mm.

8. A high-load-bearing engineering plastic worm gear for use in a light truck electric power steering system, prepared by the process of any one of claims 1 to 7, characterized in that: The engineering plastic worm gear comprises: The worm gear matrix is ​​a polyetheretherketone composite material with a density of 1.45-1.55g / cm³; The gear tooth structure includes an involute tooth profile, a pressure angle of 19.5°-20.5°, and a helix angle of 15-25°; The inner wall of the hub is provided with reinforcing ribs, and the rib thickness is 0.8-1.2 times the wall thickness.

9. The high-load-bearing engineering plastic worm gear for light truck electric power steering system according to claim 8, characterized in that: The worm gear tooth surface has a micro-texture structure: The surface is covered with micro-pits with a diameter of 50-100 μm and a depth of 10-30 μm; The pit density is 100-200 / mm², arranged in a spiral array; The pits are filled with a molybdenum disulfide solid lubricating film with a thickness of 2-5 μm.

10. The high-load-bearing engineering plastic worm gear for light truck electric power steering system according to claim 8, characterized in that: The engineering plastic worm gear meets the following requirements: At a working temperature of 120°C, the bending strength is greater than 180MPa and the compressive strength is greater than 200MPa; When meshing with a metal worm, the noise level is less than 65dB(A)@3000rpm; Chemical corrosion resistance: After immersion in gear oil for 500 hours, the mass change rate meets 0.3%.

Citation Information

Cited By

  • Magnetic carbon fiber modified PEEK material, gear prepared from magnetic carbon fiber modified PEEK material and method

    CN120988452A

  • Method for weakening crystallinity of two-dimensional photoelastic sample through structure fine tuning

    CN122282430A